O atendimento psicanalítico do bebê com risco de autismo e de outras graves psicopatologias: uma clínica da antecipação do sujeito - Isabela Santoro Campanario (2006)
The author proposed a theoretical and clinical articulation capable of providing support to an earlier psychoanalytical intervention to babies at risk of autism and other severe psychopathologies, as shown by signs of difficulty in establishing mother/child bonds, which could restrict the birth of the subjectivity in the infant. Interdisciplinary professionals that treat autistic children agree that the timing of the beginning of the treatment is essential for accomplishing the best results, which is explained by Medicine because of childrens greater cerebral neuroplasticity. How could psychoanalysis explain such fact, since psychoanalysis time is logical, not chronological? This study researched the concept ofautism in psychiatry, reviewing the latest classifications that show autism as a phenomenological sign only, which increases enormously the incidence of the syndrome. This study inquired about the usefulness of the opposition between psychogenesis and organogenesis in autism, which may explain why so little has been accomplished in termsof its treatment. We provided some developmental signs for early detection of autism, aiming not at an earlier diagnosis, but at an earlier intervention. According to psychoanalysis, labeling children early through a diagnosis could lock them into a pathology that is otherwise still changeable, especially through early intervention. This study discussed some clinical cases of psychoanalytical authors that were fundamental inproviding insight to the approach proposed here: Dick ( by M. Klein), Timmy (by D. Meltzer), Marie- Françoise ( by R. & R. Lefort ), Marina ( by M. C Laznik). It was observed that, in cases treated by Psychoanalysis, the earliest interventions reached better evolution than interventions tried when children were older. However, cases that were diagnosed early by Psychiatry, as two of the eleven Kanners inaugural cases, did notevolve better than cases of children diagnosed later. We supposed that an earlier psychiatric diagnosis could make a nomination to children who show problems in establishing the symbolism. The psychoanalytical diagnosis, however, develops over many sessions undertransference, considering how the interdiction is accepted by the subject. On the second chapter, we showed the importance of the motherese in the birth of childrens subjectivity. One case of autism of our own clinical practice (case Maurício), which started treatment many years after the crystallization of the structure, was discussed. In the third chapter, a clinical case of a child at risk of autism (John) and two other cases of severe psychopathologies in the infancy were described (cases Rafael and Lúcio). All these cases are still in treatment in Belo Horizonte, through a project called Timely Intervention. The objective of a Psychoanalytical intervention in early infancy is to (re) establish amother/baby bond through playing, where the supposition of a subject is essential. In the last chapter, it was inquired whether our clinic is preventive or anticipative. We followed showing the particularities of time in the first infancy. The present work suggests a counterpoint to the dissolution of childhood as proposed by structuralistic psychoanalyticalapproaches.